DevOps for Digital Leaders Reignite Business with a Modern DevOps-Enabled Software Factory - Ravichandran, Aruna (Springer Nature, 2016)
DevOps; continuous delivery; software lifecycle; concurrent parallel testing; service management; ITIL; GRC; PaaS; containerization; API management; lean principles; technical debt; end-to-end automation; automation